“You Are the Best Person to Defend Our Country.” The Model of Compulsory Military Service in Finland - Wywiał, Przemysław (Roczniki Nauk Społecznych, 2025)
The aim of this article is to discuss the model of compulsory military service in Fin-land, so the following research questions were posed: 1. What is the holistic security concept underlying Finland’s security strategy? 2. What is the legal basis of compulsory military service in Finland? 3. How is compulsory military service implemented? 4. What does reserve service look like? The research methods used in this article include analysis, synthesis and inference. It is concluded that common compulsory military service is one of the most important elements of Finland’s overall security concept. The vast majority of men do military service, which is consistently highly prestigious, enjoying strong public support. This is due to both the perception of existing security threats and the national character of Finns and the sense of responsibility for the country.